Institutional Design and Implicit Incentives in Bolivia's Decentralization Model - Gover Barja Daza; Sergio Villarroel Böhrt; David Zavaleta Castellón (Revista Latinoamericana de Desarrollo Económico, 2013)
The second generation fiscal federalism (SGFF) approach is used as a reference to analyze the political and fiscal institutional design of Bolivia's decentralization model and its evolution. Subnational public finance data up to 2008 is used to verify that decentralization of expenditure was higher than that of revenue, establishing a context of vertical fiscal imbalance that increased due to growing fiscal transfers during the positive external shock (boom) period. Consequently, the subnational fiscal surplus was not a result of internal efficiency but of excess revenues from such transfers. Panel models were estimated to identify and assess the implicit incentives embedded in fiscal institutions of the decentralization model.Findings at the municipal level are: i) misalignment of local spending with local interests due to dominance of transfers over own revenue (dominance of central government development policies); ii) incentive to spend transfers faster than own revenue (flypaper effect); iii) greater marginal contribution of own revenue to positive fiscal balances compared to transfers, thus introducing the seed for a soft budget constraint but hidden by the fiscal surplus; iv) disincentive to generate own revenue (tax and non-tax) due to the size and growth of transfers (disincentive to the culture of contributing to own revenue). Findings at the prefectural level are: i) misalignment with regional interests given the dominance of transfers over own revenue due to absolute lack of tax powers (until 2009); ii) high tendency to a soft budget constraint and, eventually, also fiscal bail-out, hidden by the fiscal surplus; iii) in only two departments collection of national-level taxes were higher, compared to transfers received in the same departments; iv) disincentive to pay the VAT (national-level tax) due to higher royalty transfers received, an effect not extended to other national-level taxes; v) high dependence from hydrocarbon-based transfers, and fiscal risk when this natural resource declines (both in volume and prices) due to volatility of international oil prices. Also, as a result of the decentralization model a positive and significant impact was found on education-coverage indicators, an important development objective of the national government.
Additional information: Research financed by Fundación PIEB.
Keywords: 330; Second generation fiscal federalism; Panel models; Bolivia